Fatigue strength improvement of selective laser melted Ti6Al4V using ultrasonic surface mechanical attrition. Issue 8 (3rd August 2019) - Yan, Xingchen; Yin, Shuo; Chen, Chaoyue; Jenkins, Richard; Lupoi, Rocco; Bolot, Rodolphe; Ma, Wenyou; Kuang, Min; Liao, Hanlin; Lu, Jian; Liu, Min
ABSTRACT: Ultrasonic surface mechanical attrition treatment (SMAT) was employed to modify the surface microstructural layer of SLM Ti6Al4V ELI biomedical material to improve the fatigue performance. The SMAT method can introduce a nanostructured layer in the SLM sample surface by imposing high-strain-rate plastic deformation. The nanostructured layer improves the mechanical strength of the SMAT-affected zone and induces compressive residual stress parallel with the surface which suppress the initiation of cracks. As a result, the specimen after SMAT exhibits significantly higher fatigue strength than the non-treated sample in both low- and high-cycling regime. GRAPHICAL ABSTRACT: IMPACT STATEMENT: This research demonstrates that surface mechanical attrition treatment (SMAT) is a promising post-processing technology for selective laser melting. SMAT improves the fatigue strength of selective laser melted Ti6Al4V by 100%.